Early Maladaptive Schema-Related Impairment and Co-Occurring Current Major Depressive Episode-Related Enhancement of Mental State Decoding Ability in Borderline Personality Disorder - Unoka Zsolt; Fogd Dóra; Seres Imola; Kéri Szabolcs; Csukly Gábor (2015)
Disturbed interpersonal relationships specific to borderline personality disorder (BPD) suggest biased processing of social information. The goal of this study was to examine alterations in mental state decoding (MSD) and their associations with early maladaptive schemas (EMS) that may lead to the misinterpretation of incoming information. In addition, the authors' aim was to evaluate the effects of a co-occurring current major depressive episode (MDE) on the MSD performance of BPD patients. Seventy-eight BPD patients (34 with MDE) and 76 matched healthy controls (HC) were assessed for Reading the Mind in the Eyes Test (RMET) and the level of EMS. The authors found that impairment in the total RMET performance, as well as specific impairment regarding the recognition of positive and neutral items, was associated with EMS, and enhanced vigilance to negative mental states was characteristic to BPD with MDE. Results suggest that MSD ability is altered in two independent ways in BPD.